Assessing Psychodynamic Conflicts and Level of Personality Functioning in Women Diagnosed With Vaginismus and Dyspareunia - Koops, Thula U.; Wiessner, Christian; Ehrenthal, Johannes C.; Briken, Peer (Frontiers in Psychology, 2021)
Knowledge on etiological and risk factors of genito-pelvic pain/penetration disorder, formerly classified as dyspareunia and vaginismus, is limited. The Operationalized Psychodynamic Diagnosis (OPD) system offers a valuable basis for developmental considerations, and has not yet been used to research sexual pain difficulties in women. We conducted an exploratory pilot study of psychodynamic motivational conflicts and level of personality functioning as defined by the OPD system by means of an anonymous online survey among 24 women who had been diagnosed with dyspareunia or vaginismus. We matched them with 24 healthy controls and compared groups using paired-samples t-tests and Wilcoxon tests. Effect sizes were calculated using Pearson's r. Large effect sizes were found for mean or median differences of several OPD Structure Questionnaire (OPD-SQ) scales (self-reflection, p = 0.002/r = 0.59; affect differentiation, p = 0.007/r = 0.53; self-perception, p = 0.002/r = 0.58; impulse control, p = 0.007/r = 0.53; self-worth regulation, p = 0.008/r = 0.52; self-regulation, p = 0.004/r = 0.56; experiencing affect, p = 0.009/r = 0.53; bodily self, p = 0.008/r = 0.54; OPD-SQ total score, p = 0.007/r = 0.52; internal communication, p = 0.001/r = 0.63) and OPD Conflict Questionnaire (OPD-CQ) scales (guilt conflict active, p = 0.004/r = 0.60; Oedipal conflict passive, p = 0.009/r = 0.51; individuation versus dependency conflict active, p = 0.01/r = 0.52; guilt conflict passive, p < 0.001/r = 0.70; self-worth conflict passive, p = 0.001/r = 0.70; passive mode, p < 0.001/r = 0.68). The problems with personality functioning and more pronounced types of conflicts participants displayed suggest proneness for self-invalidation, internalization and restricted self-perception.